Study on limited slip differential for cars / Mohd Ismail Mohd Nor ... [et al.] - Mohd Nor, Mohd Ismail; Abd Razak, Mohd Faizulakma; Muradi, Nor Mohammad Jailani; Haron, Mohd Fairuz (2002)
The technology of limited slip differential has been applied to the passenger cars since 20 years ago. Manufacturers found that it is beneficial for them to install the limited slip differentials in their car manufacturing to increase their performance thus attracting more buyers. Through continuous research conducted by the manufacturers, many types of limited slip differentials can be found in the current market Each of them offers different kind of characteristics to meet different demands of the car drivers. Though it is well accepted in the market, people are lacking in their knowledge about it. This study is set to reveal the secrets about the limited slip differential. These secrets include their main parts, usages, characteristic and etc. The study on limited slip differentials is very important as they have a wide usage in modern passenger cars.